BEBERAPA TEOREMA KEKONVERGENAN PADA INTEGRAL RIEMANN - Ilwaru, Venn Y. I.; Wattimanela, Henry J.; Talakua, Mozart W. (PATTIMURA UNIVERSITY, 2012)
Riemann Integral is integral concept using the sum of lower Riemann and upper Riemann. The sufficient condition for the function sequence which is R-integralable at ï›a, bï is thelimit function also R-integralable at ï›a, bï. If function sequence ï» ï½ n f convergence to f at ï›a, bï and n f R-integralable for every n, then the sufficient condition that function f alsoR-integralable at ï›a, bï is ï» ï½ n f uniform convergence to f at ï›a, bï. This research studies about sum convergence theorems in Riemann Integral.